2008
DOI: 10.1074/jbc.m708624200
|View full text |Cite
|
Sign up to set email alerts
|

DEC1, a Basic Helix-Loop-Helix Transcription Factor and a Novel Target Gene of the p53 Family, Mediates p53-dependent Premature Senescence

Abstract: Cellular senescence plays an important role in tumor suppression. p53 tumor suppressor has been reported to be crucial in cellular senescence. However, the underlying mechanism is poorly understood. In this regard, a cDNA microarray assay was performed to identify p53 targets involved in senescence. Among the many candidates is DEC1, a basic helix-loop-helix transcription factor that has been recently shown to be up-regulated in K-ras-induced premature senescence. However, it is not clear whether DEC1 is capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
107
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 46 publications
12
107
0
Order By: Relevance
“…We previously showed that DEC1, a target of p53, mediates G1 arrest and premature senescence in p53-and p21-independent manners (16). In this study, we showed that DEC1 inhibits DNA damage-induced apoptosis in a p53-dependent manner.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…We previously showed that DEC1, a target of p53, mediates G1 arrest and premature senescence in p53-and p21-independent manners (16). In this study, we showed that DEC1 inhibits DNA damage-induced apoptosis in a p53-dependent manner.…”
Section: Discussionsupporting
confidence: 51%
“…DEC1 is defined as a senescence marker because it is up-regulated in premalignant tumors (15). Consistent with this, our previous studies showed that DEC1 is a target of the p53 family and mediates G1 cell cycle arrest and DNA damage-induced premature senescence (16,17). Evidence also showed that DEC1 plays a role in cell death.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Cells seeded on a six-well plate were uninduced or induced to express RNPC1a for 6 days. The senescence assay was performed as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…Under unstressed condition, p53 protein is maintained at a low level mostly through ubiquitinationmediated proteosomal degradation (2). In response to DNA damage and other stress signals, p53 is activated and functions as a transcription factor to induce its downstream targets for various cellular processes such as cell cycle arrest [p21, growth arrest and DNA-damage-inducible protein 45 (GADD45)] (3,4), apoptosis [p53 up-regulated modulator of apoptosis protein (PUMA), insulinlike growth factor binding protein 3 (IGFBP3), DR5] (5-7), and senescence [plasminogen activator inhibitor-1 (PAI-1), differentially expressed in chondrocytes protein 1 (DEC1)] (8,9). Although many p53 target genes related to various cellular processes have been identified, these are still insufficient to explain how p53 exerts its functions, in particular cellular senescence.…”
mentioning
confidence: 99%